Intelligent Decision Support System for Transport Infrastructure Investment with Emphasis on Joint Logistic Concept - Abdalla Alameen, Dr.; Ashu Gupta, Dr. (International Journal of Engineering and Technology, 2018)
The point of this proposal is to give to the legislative chief/client, an instrument that can help him/her in enhancing the foundation speculation choice in the efficient, ecological and maintainable angles. This implies, the Return on Investment (ROI) of the concerned transport framework, fulfilling natural and maintainable imperatives must be certain, and comparing to an ideal venture cost. The choice emotionally supportive network can be connected in two measurements. One measurement is the place the genuine arrangement process is happening among private and open partners, called "ongoing transaction process". The second measurement is the place the arrangement procedure is induced by the client (open part) without private partners communication (yet with association through re-enactment), called "virtual transaction process". The re-enactment and nearby advancement procedures, in stage with operator innovation, utilized in the "virtual transaction process" empower us to accomplish a specific measure of elective choices to the essential/proposed choice to be assessed.Â Â